Organizational behaviour and change in Europe : case studies - Chevalier, Françoise; Segalla, Michaël (European management series., 1996)
This stimulating case-study volume addresses key issues in organizational behaviour, organizational change and human resource management in a range of European organizations, including international companies in and from Europe. Its consistent emphasis is organizational change in a shifting, 'internationalizing' world and sensitivity to the impact of different cultures on the problems as they are defined as well as on their solutions. The carefully selected cases are longer and richer than is usual in this area, thus capturing more realistic breadth and complexity, including firm location of 'OB' and 'HRM' themes in the context of the broader market and other issues facing the organizations concerned. The themes covered include: managing growth and 'Europeanization'; managing decline and crisis; transforming cultures; organization design leadership, autonomy and control, organizational learning and change.